Thio-Pybox and Thio-Phebox complexes of chromium, iron, cobalt and nickel and their application in ethylene and butadiene polymerisation catalysis. - Nobbs,JD; Tomov,AK; Cariou,R; Gibson,VC; White,AJP; Britovsek,GJP (Dalton Trans., 2012)
Seven bis(thiazolinyl)- and bis(thiazolyl)pyridine Thio-Pybox ligands and their metal complexes of Cr(III), Fe(II), Co(II) and Ni(II) were prepd., as well as a Ni(II) complex contg. a monoanionic bis(thiazolinyl)phenyl Thio-Phebox ligand. These new metal complexes were characterized and used as catalysts, in combination with the co-catalyst MAO, for the polymn. of ethylene and for the polymn. of butadiene. In the case of ethylene polymn., the Thio-Pybox and Thio-Phebox metal complexes showed relatively low polymn. activities, much lower compared to the related bis(imino)pyridine complexes of the same metals. In the polymn. of butadiene, several Thio-Pybox Co(II) complexes show very high activities, significantly higher than the other metal complexes with the same ligand. It is the metal, rather than the ligand, that appears to have the most profound effect on the catalytic activity in butadiene polymn., unlike in the polymn. of ethylene, where bis(imino)pyridine ligands provide highly active catalysts for a range of 1st row transition metals. The mol. structures of one ligand and eight complexes were detd. by x-ray crystallog. [on SciFinder(R)]